(untitled) (Bangladesh Journal of Agricultural Research, 2014)
An experiment was conducted at Bangladesh Rice Research Institute (BRRI), Gazipur during T.Aman season of 2007 with a view to evaluating seven maintainer and 30 restorer lines for yield and yield contributing characters for selecting promising maintainer and restorer lines for developing rice hybrids in our local environment. Significant variations were noticed among the parental lines for all the characters studied. The CMS lines Gan46A and BRRI9A could be used as female parents in hybrid seed production due to good yield and yield contributing characters recorded in their corresponding maintainer lines. Restorer line BR168R could offer high yield potentiality in heterosis breeding due to its superior yield contributing characters in local environment. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18868 Bangladesh J. Agril. Res. 38(4): 553-562, December 2013